Solvency vs Information Asymmetry vs Intellectual Capital: Who Wins in Earnings Manufacturing Management? - Eogenie Lakilaki; Tri Wahyuni; Muhammad Andrian Irsa; Khoirur Rijal (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This study addresses the research problem of inconsistent empirical findings regarding the determinants of earnings management, particularly the roles of information asymmetry, intellectual capital, and leverage in Indonesian manufacturing firms. Despite extensive prior research, limited consensus exists on how these factors simultaneously influence managerial discretion in financial reporting. This study aims to examine the interplay among these variables in shaping earnings management practices. Adopting a quantitative design, this study utilises balanced panel data from manufacturing companies listed on the Indonesia Stock Exchange over the period 2015–2024. The analysis employs a Fixed Effects Model, selected through Chow and Hausman tests, to control for unobserved heterogeneity across firms. The findings indicate that information asymmetry has a statistically significant negative effect on earnings management, suggesting that improved transparency constrains opportunistic reporting behavior, while intellectual capital and leverage exhibit statistically significant positive effects, indicating that firms with greater intangible resources and higher financial pressure are more likely to engage in earnings management practices. Overall, this study provides stronger empirical support that earnings management is shaped by informational conditions, firm capabilities, and financial constraints, offering important implications for strengthening corporate governance and enhancing the reliability of financial reporting in emerging markets.